Smart hose power / Muhammad Heedir Shamsulkamar, Ahmad Fuad Omar and Mohd Jawahir Ahmad Ramli - Shamsulkamar, Muhammad Heedir; Omar, Ahmad Fuad; Ahmad Ramli, Mohd Jawahir (2018)
"Make toilet great again" is our company motto that brings the idea of this project. Through observation, our company can conclude that toilet hygiene and tidiness is always taken for granted by several people. Towards the year 2020, our company take the initiative to bring technology into toilet. Our company is honoured to be the first ever company come out with the idea of Smart Water Hose. This product can promote a healthier and more hygienic toilet.